2017
DOI: 10.1007/s12178-017-9417-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Education for Hip and Knee Replacement: Never Stop Learning

Abstract: Purpose of reviewParticipation in alternative payment models has focused efforts to improve outcomes and patient satisfaction while also lowering cost for elective hip and knee replacement. The purpose of this review is to determine if preoperative education classes for elective hip and knee replacement achieve these goals.Recent findingsRecent literature demonstrates that patients who attend education classes prior to surgery have decreased anxiety, better post-operative pain control, more realistic expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 96 publications
4
102
0
2
Order By: Relevance
“…[56][57][58] A recent review article discusses how the spaced retention education method for rapid recovery total joint arthroplasty can be incorporated in a busy joint arthroplasty practice. 59 In response to recent discussions with CMS, AAHKS has offered the following evidence-based patient selection criteria to identify patient criteria for safe same-day discharge to home. To be considered for same-day discharge, a patient should undergo a thorough evaluation by the physical therapy team, demonstrating the ability to safely ambulate with assistance to and from the bathroom, ascend and descend two steps, and walk independently on ground level using an assistive device.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] A recent review article discusses how the spaced retention education method for rapid recovery total joint arthroplasty can be incorporated in a busy joint arthroplasty practice. 59 In response to recent discussions with CMS, AAHKS has offered the following evidence-based patient selection criteria to identify patient criteria for safe same-day discharge to home. To be considered for same-day discharge, a patient should undergo a thorough evaluation by the physical therapy team, demonstrating the ability to safely ambulate with assistance to and from the bathroom, ascend and descend two steps, and walk independently on ground level using an assistive device.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of such interventions concluded that pre‐operative education reduces anxiety, postoperative pain and length of stay, and improved satisfaction . Such programmes have been incorporated into routine care for joint arthroplasty , and are an integral element of enhanced recovery after surgery pathways that have been demonstrated to improve surgical outcomes . More recently, surgery schools have been incorporated into enhanced recovery programmes, with apparent beneficial effects on outcomes, although it is not clear which elements of the package of care are most effective .…”
Section: Pre‐operative Education Programmesmentioning
confidence: 99%
“…Patients undergoing TJR may experience improved surgical outcomes and decreased anxiety when they attend preoperative education classes that address prevention of infections and venous thromboembolism (VTE), early ambulation, pain management, and rehabilitation needs (eg, procuring durable medical equipment) . Preoperative patient education providers should consider the learning needs and reading levels of their patients (ie, health literacy) when developing brochures and other written material.…”
Section: Preoperative Phase Of Carementioning
confidence: 99%